The Fading Spirit of Nationalism in the Digital Native Generation Due to the Effect of Westernization - Susan Nurlaelasari; Yulia Amanda; Silvi Amelia Widyarti; Diki Okdiansyah; Ahmad Fuadin (CV. Rayyan Dwi Bharata, 2023)
This study aims to provide an overview of the fading spirit of nationalism in the digital native generation due to the influence of westernization. The research method uses a qualitative and quantitative approach with a case study method that focuses on understanding the fading spirit of nationalism in the digital native generation due to the influence of westernization. The informants of this study were lecturers in the Social Sciences Education at the Indonesian University of Education and young people from the digital native generation using interview techniques. The phenomenon of westernization or imitating Western culture has developed massively in Indonesia. This is a threat to the fading of the spirit of nationalism in the digital native generation, due to the melting of Western culture with authentic Indonesian culture. The biggest agent in this phenomenon is the younger generation, especially the digital native generation who are friendly with technology. Love for the motherland is expected to be a shield for the swift currents of westernization brought about by globalization. The results of the study show that the younger generation already understands a sense of nationalism, namely love for the motherland, but they also reveal that westernization can affect the fading of the spirit of nationalism in the younger generation, especially the digital native generation, so there is a need for policies to deal with this problem from various parties.